1983
DOI: 10.1002/jcp.1041140112
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic proteins of the 3T3 plasma membrane

Abstract: A mitogenic factor from 3T3 plasma membranes has been identified and partially characterized. The factor appears to be a peripheral membrane protein that can be released by mild trypsin, chymotrypsin, or plasmin treatment. This component is sensitive to heat and acid, and has a molecular weight in the range of 150,000-200,000 daltons as determined by gel filtration. A similar mitogenic activity has also been found on the membranes of both SV-40-transformed 3T3 cells and human fibroblasts. The factor appears to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

1984
1984
1994
1994

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
1
8
1
Order By: Relevance
“…A 150,000-Da trypsin-releasable mitogenic activity associated with 3T3 plasma membranes has been reported by Lieberman (18). The active component described here is much smaller than this factor and is different in its potency, acid resistance, and DEAE-cellulose elution characteristics.…”
supporting
confidence: 48%
“…A 150,000-Da trypsin-releasable mitogenic activity associated with 3T3 plasma membranes has been reported by Lieberman (18). The active component described here is much smaller than this factor and is different in its potency, acid resistance, and DEAE-cellulose elution characteristics.…”
supporting
confidence: 48%
“…In this report, we describe the observation that heparin can also potentiate the action of plasma membraneassociated growth stimulatory activity (PMGA), which is found in a high-salt extract of cellular plasma membranes (Lieberman, 1983(Lieberman, ,1984. By using a pyrophosphate extract of mouse liver plasma membranes, we have found that the action of heparin can be mimicked by several sulfated polysaccharides.…”
mentioning
confidence: 89%
“…The next group of growth inhibitors encompasses peptide factors isolated from plasma membrane fractions of resting cultured cells (Whittenberger & Glaser 1977, Datta & Natraj 1980, Lieberman 1983. Similar fractions from growing cells lack the inhibitory activity.…”
Section: Cell-associated Inhibitorsmentioning
confidence: 99%
“…A human cdc2.5 homologue essential for mitosis has also been identified (Millar et al 1991, Strausfeld et al 1991. Conversely, the products of two genes, weel and mikl (both kinases) are negative regulators of ~3 4 '~" " , phosphorylating it on tyrosine residues and thus preventing the onset of mitosis (Lundgren et al 1991). The negative effects of the weel gene can be overridden by the product of another gene, niml kinase (Russell & Nurse 1987, Wu & Russell 1993, Parker et al 1993, whereas the products of the pypl and pyp2 genes (both tyrosine phosphatases) contribute to the inhibition of mitosis by enhancing the activity of weel kinase (Millar et al 1992).…”
Section: T H E G/m Transitionmentioning
confidence: 99%